A techno-economic analysis of an optimal self-sufficient district. (15th May 2021) - Laitinen, Ari; Lindholm, Oscar; Hasan, Ala; Reda, Francesco; Hedman, Åsa
Graphical abstract: Results of the optimization model showing optimum investment cost of different components of the investigated energy system for different energy self-sufficiency rates of the district. Highlights: A techno-economic study of renewable energy in a district with high self-sufficiency. Two methods are used: a rule-based method and an optimization method. The self-sufficiency rate has a significant impact on the life cycle cost. In the Nordic region, the main investment should be made in wind power. The district's physical boundary may need to extend to a virtual boundary. Abstract: Many cities and districts have announced that their ultimate goal is to be energy self-sufficient, but there are many technical and economic challenges that are required to be studied. The aim of this study is to find cost-optimal technical solutions for districts with high energy self-sufficiency rates that can cover their electricity demand. Two methods are applied, a rule-based method and an optimization method, to find the renewable energy system capacities for local centralized wind power, solar photovoltaic, battery, heat storage and heat pump in a district with a minimum life cycle cost. The Kalasatama district in Helsinki-Finland, is taken as a case study. The results show that the full energy self-sufficiency target requires very high investments in the renewable energy systems. For the studied case, reducing the self-sufficiency rate to 76% can bring down the life cycle cost by 66% and achieve a net-zero annual energy balance. It is economically and technically more feasible to aim achieving Positive Energy District or Net-Zero Energy District instead of full energy self-sufficiency. Based on the obtained results, the main investment should be made in wind power, due to its higher utilization rate around the year compared to solar photovoltaic. Investments in the expensive centralized battery storage sharply drops when the self-sufficiency rate is reduced from 100%. It is revealed that due to the high population density and limited availability of renewables, the physical boundary of a district may not fit the required renewable energy installations if high self-sufficiency is targeted. This will frequently lead to expanding the district boundary towards a virtual balancing boundary.